The Godwinian letter: William Godwin's epistolary exchanges, 1778-1805 - Wood, J (2019)
The resurgence in scholarly recognition of William Godwin’s (1756-1836) centrality in the final decades of the eighteenth century has given new significance to his private writings. The recently activated online Godwin Diary (2010), hosted by the Oxford Digital Library at the Bodleian, is an invaluable record of Godwin’s day-to-day routine from 1788 to his death in April 1836. In addition, the publication of the first two volumes of a projected six- volume edition of Godwin’s extant letters (OUP, 2011—), edited by Pamela Clemit, restores access to various neglected lines of inquiry in Godwin criticism – in particular his epistolary exchanges.